Correspondances. Paul Klee, Pierre Boulez e Jacques Maritain: quale contributo alla riflessione pedagogica e alla prassi educativa? - Albarea, Roberto (Studi sulla Formazione/Open Journal of Education, 2019)
This contribution intend to start by the hypothesis that the Music experience and the educational dimension of Art, a cause of its peculiar languages and especially if they are supported from a founded educational vision, can be a substratum where a dynamic and pluralistic thinking is capable of balancing conflicts, contradictions and diversities; a sort of attitude in front of things, nature and people, which, on the one hand, is aware of the contradictions of existence and it knows the role of variables, antinomies and paradoxes (sometimes lacerating), and, on the other, it accepts to be accompanied with they, conceived as elements of the individual existence in front of contemporary experience. Correspondences between the writings of a painter, a musician and a philosopher can give a new light to the theme about creativity in education.